2020
DOI: 10.1590/1516-4446-2019-0630
|View full text |Cite
|
Sign up to set email alerts
|

DRD4 genotyping may differentiate symptoms of attention-deficit/hyperactivity disorder and sluggish cognitive tempo

Abstract: Objective: Studies to reduce the heterogeneity of attention-deficit/hyperactivity disorder (ADHD) have increased interest in the concept of sluggish cognitive tempo (SCT). The aim of this study was to investigate if the prevalence of two variable-number tandem repeats (VNTRs) located within the 3′-untranslated region of the DAT1 gene and in exon 3 of the dopamine D4 receptor ( DRD4 ) gene differ among four groups (31 subjects with SCT but no AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…SNPs in DRD 4 relate to distinct domains of ADHD severity ( Cervantes-Henríquez et al, 2022 ). The 7R allele of the DRD4 gene is more prevalent in sluggish cognitive cases than in ADHD cases ( Bolat et al, 2020 ). It has been reported that the interaction between the methylation of CpG sites of DRD4 (CpG26 and CpG28) and phthalate metabolite levels can affect the attention level in ADHD patients ( Kim et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…SNPs in DRD 4 relate to distinct domains of ADHD severity ( Cervantes-Henríquez et al, 2022 ). The 7R allele of the DRD4 gene is more prevalent in sluggish cognitive cases than in ADHD cases ( Bolat et al, 2020 ). It has been reported that the interaction between the methylation of CpG sites of DRD4 (CpG26 and CpG28) and phthalate metabolite levels can affect the attention level in ADHD patients ( Kim et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…ADHD etiology is complex and strongly related to neurotransmitter pathways, i.e., dopamine [42]. Family-based and genome-wide association studies (GWAS) have identified single nucleotide polymorphisms (SNPs) in the DRD4 gene associated with ADHD [43,[79][80][81][82][83][84][85]. Furthermore, genetic variants in the FGF1 [17,52] and ADGRL3 (LPHN3) [17,52,58,59,83,[86][87][88][89][90][91][92][93] genes are associated with ADHD and ADHD endophenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an analysis of both patients and the literature found an association of the 10-repeat/10-repeat genotype with ADHD only in adolescents [ 85 ], studies performed in children reported an association between the 10-repeat/10-repeat genotype and ADHD [ 86 , 87 ], while a recently published meta-analysis reported an association of the 10-repeat allele with ADHD in children and adolescents, specifically in European population [ 88 ]. However, there are also reports indicating no association at all between ADHD and the VNTR of DAT gene (9-repeat/10-repeat, 10-repeat/10-repeat, and 10-repeat/11-repeat genotypes) [ 89 ], no association between the 10-repeat/10-repeat allele with ADHD [ 90 ], and no association between ADHD and the 9-repeat or the 10-repeat alleles for this polymorphism [ 91 ]. The last three studies were performed in children.…”
Section: Genetic Factors Associated With Adhdmentioning
confidence: 99%